Implementasi Kewenangan Penyelenggaraan Perizinan Berusaha di Daerah dalam Rangka Meningkatkan Investasi di Kota Bekasi Menurut Peraturan Pemerintah Nomor 6 Tahun 2021 Tentang Penyelenggaraan Perizinan Berusaha di Daerah - Samsuri, Samsuri; Juanda, Juanda; Atmoko, Dwi; Juanda, Ogiandhafiz (Green Publisher, 2023)
This research is to find out the implementation of business licensing authority in the regions to increase investment in Bekasi City according to Government Regulation Number 6 of 2021 concerning the Implementation of Business Licensing in the Regions and to find out what the juridical consequences are for regions that do not guide/do not make adjustments according to Government Regulation Number 6 Year 2021 Concerning the Implementation of Business Licensing in the Regions. The type of legal research used is empirical normative legal research that uses primary legal materials, secondary legal materials, and tertiary legal materials with data collection through library research using qualitative analysis methods. The results of the study show that the authority to administer business licensing in the city of Bekasi to increase investment, when referring to government regulation number 6 of 2021 concerning the implementation of business licensing in the regions, does not yet have an operational legal basis for implementation in the form of regional regulations governing business licensing, so it is still There are legal cases in particular, the implementation of business licensing is currently still based on Mayor Regulation number 52 A of 2021 concerning risk-based business licensing but has not linked it to a higher regulation, namely a regional regulation.